2020
DOI: 10.4149/neo_2019_190306n191
|View full text |Cite
|
Sign up to set email alerts
|

MiR-378a-5p inhibits angiogenesis of oral squamous cell carcinoma by targeting KLK4

Abstract: Oral squamous cell carcinoma (OSCC) is still a leading cause of cancer death owing to distant metastasis, which is largely facilitated by tumor angiogenesis. MicroRNA (miR)-378a-5p and Kallikrein-related peptidase 4 (KLK4) participate in tumorigenesis and tumor metastasis according to previous studies, yet the exact role they play in tumor angiogenesis remains poorly understood. The aim of the present study was to investigate the effect of miR-378a-5p and KLK4 on angiogenesis of OSCC. MTT assay showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Pan et al ( 46 ) found that miR-378a-5p was reduced in renal tissues and renal cell carcinoma cells, and patients with a high miR-378a-5p level exhibited longer overall survival rates than those of patients with low miR-378a-5p levels. In addition, previous reports have demonstrated that miR-378a-5p is implicated in the regulation of metabolism and angiogenesis ( 43 , 47 ). The present study found low expression of miR-378a-5p in ESCC tissues, and this was closely associated with TNM stage and lymph node metastasis, suggesting that the LINC00514/miR-378a-5p signaling axis may be an important therapeutic target for patients with ESCC.…”
Section: Discussionmentioning
confidence: 92%
“…Pan et al ( 46 ) found that miR-378a-5p was reduced in renal tissues and renal cell carcinoma cells, and patients with a high miR-378a-5p level exhibited longer overall survival rates than those of patients with low miR-378a-5p levels. In addition, previous reports have demonstrated that miR-378a-5p is implicated in the regulation of metabolism and angiogenesis ( 43 , 47 ). The present study found low expression of miR-378a-5p in ESCC tissues, and this was closely associated with TNM stage and lymph node metastasis, suggesting that the LINC00514/miR-378a-5p signaling axis may be an important therapeutic target for patients with ESCC.…”
Section: Discussionmentioning
confidence: 92%
“…For example, by binding to the 3'-UTR of suppressor of fused homolog (SUFU), miR-378a-5p promoted cell apoptosis in triple negative breast cancer [22]. In oral squamous cell carcinoma, miR-378a-5p was shown to be negatively associated with the cell proliferation and inhibited angiogenesis through binding to kallikrein-related peptidase 4 (KLK4), inhibiting tumorigenesis and tumor metastasis [23]. Therefore, the overexpression of miR-378a-5p benefits the prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu P et al reported that the interaction of hsa_circ_0004018 and miR‐626/DKK3 with HCC proliferation and migration and xenograft tumor growth involves the Wnt/β‐catenin signaling pathway 11 . Additionally, aberrations in Wnt/β‐catenin are common during human carcinogenesis, which suggests that Wnt/β‐catenin is a major target for the treatment of cancers, including OSCC 51 . Mechanistically, activation of the Wnt/β‐catenin pathway is triggered by the expression of the FZD1 receptor, and the elevation of β‐catenin also indicates the activation of Wnt signaling 52 .…”
Section: Discussionmentioning
confidence: 99%